Critical analysis of the reflection by the resources quality agro-livestock in the labeling of generated foodstuff - Mnerie, Dmitriy; Gaceu, Liviu; Gubenia, Oleksii; Shamtsyan, Mark; Birca, Adriana (My University, 2015)
Nutritional labeling of food products is an important goal for ensuring the operation of a free market in both the European and adjacent area. The paper points out some limitations of European legal provisions in connection with the legislation of the countries geographically located in the Black Sea area. It is reflected by concrete examples and analyzes about the quality of agro-livestock as resources underlying healthy food. It is shown some proposals and recommendations for to improve some modalities for to highlight the role of traceability in the food product profile.
Keywords: маркування; якість; харчування; закон; кафедра машин і апаратів харчових та фармацевтичних виробництв; макрировка; качество; питание; labeling; quality; nutrition; low